EVALUATION OF QUALITY ASSURANCE PROGRAM - Murni Yanto (IJHCM (International Journal of Human Capital Management), 2017)
This study is to investigate the implementation of the evaluation program of quality assurance State Islamic High School Curup. This study design is evaluative survey. In this study, the level of implementation of the evaluation results are divided into five categories, namely: excellent, good, average, less, much less. The results of the evaluation study the implementation of quality assurance programs included in both categories. Program quality assurance Sekolah Tinggi Agama Islam Negeri Curup necessary to repair all fronts, this can be illustrated as follows: (1) Basic policy program quality assurance, (2) resource program quality assurance, (3) implementation of the guarantee program, (4) Results the achievement of a quality assurance program. The results of the study suggested the central quality assurance to be able to follow up on some of the findings, especially concerning the quality assurance program resources, training and dissemination of quality, and implement improved quality assurance program so that the process of quality assurance programs to be more effective.Keywords : Evaluation, Implementation of the quality program, CIPP